Two new sphyrapodid species (Crustacea: Tanaidacea: Apseudomorpha) from southwestern Japan - Kakui, Keiichi; Kajihara, Hiroshi; Mawatari, Shunsuke F. (Zootaxa, 2007)
Two new species, Kudinopasternakia balanorostrata and Pseudosphyrapus quintolongus are described from Japan. Kudinopasternakia balanorostrata is characterized by an acorn-shaped rostrum. It most closely resembles K. siegi (Viskup & Heard, 1989), but can be distinguished by the shape of the rostrum, the number of setae on article 2 of the mandibular palp, and the setation on the outer lobe of the fixed endite of the maxilla. Pseudosphyrapus quintolongus is characterized by an unusually large lateral process on pleonite 5, which distinguishes it from all other species in the genus. Keys to species of Kudinopasternakia and Pseudosphyrapus are given.